HIV infection is influenced by dynamin at 3 independent points in the viral life cycle. (11th April 2017) - Aggarwal, Anupriya; Hitchen, Tina L.; Ootes, Lars; McAllery, Samantha; Wong, Andrew; Nguyen, Khanh; McCluskey, Adam; Robinson, Phillip J.; Turville, Stuart G.
Abstract : CD4 T cells are important cellular targets for HIV‐1, yet the primary site of HIV fusion remains unresolved. Candidate fusion sites are either the plasma membrane or from within endosomes. One area of investigation compounding the controversy of this field, is the role of the protein dynamin in the HIV life cycle. To understand the role of dynamin in primary CD4 T cells we combined dynamin inhibition with a series of complementary assays based on single particle tracking, HIV fusion, detection of HIV DNA products and active viral transcription. We identify 3 levels of dynamin influence on the HIV life cycle. Firstly, dynamin influences productive infection by preventing cell cycle progression. Secondly, dynamin influences endocytosis rates and increases the probability of endosomal fusion. Finally, we provide evidence in resting CD4 T cells that dynamin directly regulates the HIV fusion reaction at the plasma membrane. We confirm this latter observation using 2 divergent dynamin modulating compounds, one that enhances dynamin conformations associated with dynamin ring formation (ryngo‐1‐23) and the other that preferentially targets dynamin conformations that appear in helices (dyngo‐4a). This in‐depth understanding of dynamin's roles in HIV infection clarifies recent controversies and furthermore provides evidence for dynamin regulation specifically in the HIV fusion reaction. Abstract : The concept that HIV endocytosis is the rate limiting step for HIV fusion in primary resting and activated CD4 T cell subsets has become controversial. Although dynamin plays a key role in endocytosis, modulation of its activity has led to both supportive and contradictory evidence for its role in HIV fusion. Through chemical dissection of dynamin action in the HIV life cycle of primary resting and activated CD4 T cells, we reveal that dynamin plays a role at 3 discrete stages: cell cycle related HIV transcription, the HIV fusion site and the HIV fusion reaction.